Getting acquainted: First steps for child-robot relationship formation - Ligthart, Mike E. U.; Neerincx, Mark A.; Hindriks, Koen V. (Frontiers in Robotics and AI, 2022)
In this article we discuss two studies of children getting acquainted with an autonomous socially assistive robot. The success of the first encounter is key for a sustainable long-term supportive relationship. We provide three validated behavior design elements that enable the robot to robustly get acquainted with the child. The first are five conversational patterns that allow children to comfortably self-disclose to the robot. The second is a reciprocation strategy that enables the robot to adequately respond to the children's self-disclosures. The third is a personality profile for the robot that creates more rapport and comfort between the child and the robot. The designs were validated with two user studies ($N_1$=30, $N_2$=75, 8-11 school children). The results furthermore showed similarities between how children form relationships with people and how children form relationships with robots. Most importantly, the amount of self-disclosure is an important predictor for the success of child-robot relationship formation. Self-disclosure is additionally stimulated when the robot likes what the children likes and when it displays low arousal behavior. Finally, the children's extraversion trait predicts how much they self-disclose to the robot.